Narracje rodziców młodzieży z zaburzeniami psychicznymi - Kubiak, Hanna (Studia Edukacyjne, 2020)
Kubiak Hanna, Narracje rodziców młodzieży z zaburzeniami psychicznymi [Adolescents with Mental Disorders in their Parents Narratives]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 167-184. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.9 The text is devoted to analyzing the narrative of parents of adolescents with mental disorders. Families in which young people with mental disorders are brought up are in a specifically difficult situation. Their basic assumptions regarding the safety of their existence are being undermined. They experience different emotions, usually to a large extent. Parents undergoing this special experience were offered to participate in a support group conducted with assumptions of existential and narrative psychology. The purpose of this text is to present and discuss research results, focusing on the analysis of parental narratives obtained in the described context. They concerned, among others, the adoption of psychiatric diagnosis, the relationship between parents and children, and parental identity.